Children's Rights and Education in Argentina, Chile and Spain - Poveda, David; Gómez, Viviana; Messina, Claudia (Education Policy Analysis Archives, 1999)
This article is a first attempt to relate the UN Convention on the Rights of the Child to education policy. It compares three countries, Argentina, Chile and Spain in an attempt to both present particular problems that are of pressing concern in each and to propose a framework that might reveal some possible obstacles to the implementation of children's rights. The article is divided into three sections. In the first section, a comparative review of the formal dispositions and legislative changes in the three countries is presented. Some of the most notable contrasts are briefly contextualized in the history of each nation-state. In the second section, particular problems in each nation are reassessed through the lens of the Convention. Three cases are examined: in Argentina, the funding and organization of public compulsory education; in Chile, an instance of international cooperation in education; in Spain, the relations between public and private education and ethnic segregation. Finally, a general framework is discussed using these three cases as examples.